2007
DOI: 10.1111/j.1740-0929.2007.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating environmental impacts of the Japanese beef cow–calf system by the life cycle assessment method

Abstract: The objectives of this study were to evaluate the environmental impacts of a beef cow–calf system using a life cycle assessment (LCA) method and to investigate the effects of scenarios to reduce environmental impacts on the LCA results. The functional unit was defined as one marketed beef calf, and the processes associated with the cow–calf life cycle, such as feed production, feed transport, animal management, the biological activity of the animal and the treatment of cattle waste were included in the system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
7
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 19 publications
5
92
7
6
Order By: Relevance
“…Although there is a less soil erosion in the IS due to the control of the animal's permanence in the paddocks and forage supply, there is decrease in soil cover and increased the potential losses of nutrients in the ES from the continuous selective grazing. The values obtained in this category (0.0028 and 0.0038 kg SO 2 eq/kg LWG for the ES and the IS, respectively) are different to the values found by Ogino et al (2007) in Japan (0.248 kg SO 2 eq/kg LWG), and by Nguyen et al (2010) in the EU (210 g SO 2 eq/kg HSCW, which corresponds to approximately 0.1 kg SO 2 eq/kg LWG). The appreciation of these relationships should consider the greater degree of intensity of the systems studied by these authors.…”
Section: Terrestrial Acidification and Freshwater Eutrophicationmentioning
confidence: 54%
See 3 more Smart Citations
“…Although there is a less soil erosion in the IS due to the control of the animal's permanence in the paddocks and forage supply, there is decrease in soil cover and increased the potential losses of nutrients in the ES from the continuous selective grazing. The values obtained in this category (0.0028 and 0.0038 kg SO 2 eq/kg LWG for the ES and the IS, respectively) are different to the values found by Ogino et al (2007) in Japan (0.248 kg SO 2 eq/kg LWG), and by Nguyen et al (2010) in the EU (210 g SO 2 eq/kg HSCW, which corresponds to approximately 0.1 kg SO 2 eq/kg LWG). The appreciation of these relationships should consider the greater degree of intensity of the systems studied by these authors.…”
Section: Terrestrial Acidification and Freshwater Eutrophicationmentioning
confidence: 54%
“…GHG emissions Beef production (kg) GHG intensity (kg CO 2 eq/kg) 32%e42% (Weiss and Leip, 2012), 48.16% (Mc Geough et al, 2012), and 61.2% (Ogino et al, 2007) of the total emissions, respectively. The lower fraction of enteric emissions obtained by these authors is due to the greater contribution of emissions from manure management and animal production with large amounts of concentrates.…”
Section: Global Warmingmentioning
confidence: 99%
See 2 more Smart Citations
“…The contribution of these three gases to the different activities involved in livestock farming has been estimated using the life cycle assessment method. It has been reported that enteric CH 4 is the most important GHG emitted (50% to 60%), at the farm scale, in ruminant production systems (Ogino et al, 2007). Methane represents also a significant energy loss to the animal ranging from 2% to 12% of gross energy (GE) intake (Johnson and Johnson, 1995).…”
Section: Introductionmentioning
confidence: 99%